1998
DOI: 10.1037/1089-2680.2.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Memory Beliefs as Social Cognition: A Reconceptualization of What Memory Questionnaires Assess

Abstract: Few attempts have been made to integrate research on memory beliefs across adulthood with related constructs in social cognition. This article addresses the issue of how respondents formulate answers to memory-beliefs questions from a social-cognitive perspective. We propose that reported memory beliefs represent the outcomes of a process that involves both the retrieval of previously stored information about self and about memory and on-line constructive processes. This article offers a set of assumptions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 59 publications
4
78
0
Order By: Relevance
“…McDonald-Miszczak et al, 1995;Cavanaugh et al 1998). If the factor solution presented in this paper proves to be stable, a potentially fruitful direction for future research is the investigation of age-related change in the three factors, as suggested by the Forgetfulness and Distractibility means.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McDonald-Miszczak et al, 1995;Cavanaugh et al 1998). If the factor solution presented in this paper proves to be stable, a potentially fruitful direction for future research is the investigation of age-related change in the three factors, as suggested by the Forgetfulness and Distractibility means.…”
Section: Discussionmentioning
confidence: 99%
“…An explanatory account for these findings was offered by McDonaldMiszczak, Hertzog, and Hultsch (1995), who proposed a social-cognition framework which posits that implicit knowledge about a general decline of cognitive functioning in old age might bias judgments of older persons about their own cognitive functioning towards the general expectation of decline. Similarly, Cavanaugh, Feldman, and Hertzog (1998) pointed out that memory failures may be seen as part of a common self-theory of aging: When asked about personal memory beliefs, older adults are more likely to access memory-failure concepts and to make dispositional evaluations relative to young adults or relative to one's own past.…”
Section: Cognitive Failures Across the Lifespanmentioning
confidence: 99%
“…The subjects were then asked to recall a memory to each of the remaining 30 cue words in turn and, while they were thinking about that memory, to answer the 15 questions about it. Although many factors can affect people's judgments about their memories (for reviews, see Cavanaugh, Feldman, &Hertzog, 1998, andFiore, 1997), ratings given while an activity is ongoing, in contrast to retrospective reports, reflect the cognitive processes involved in that activity in ways that produce lawful relations and relate in reasonable ways to objective measures (Ericsson & Simon, 1993), and so we obtained our ratings while our subjects were being asked to remember each autobiographical memory. This part of the task was self-paced.…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
“…Frequently, SCI measures require recall of cognition over long periods of time (e.g., years); however, this too varies across assessments. Retrospective accounts over lengthy intervals lead to bias in responses as individuals will rely on generalizations about cognition rather than specific instances of recent performance (Cavanaugh, Feldman, & Hertzog, 1998). For example, individuals may focus on the experiences related to cognition that were emotionally intense (e.g., forgetting a medication that led to medical complications) but occurred months or years earlier.…”
Section: Sci Measurementmentioning
confidence: 99%